Providing Trainees With an Introduction and Decision-Making Framework for Pursuing an Academic Residency Position - Conair Guilliames; Harsh Sule; Hector Perez; Basil Hubbi; John P. Sánchez (Association of American Medical Colleges, 2018)
Introduction Medical students are a significant source of the future academic medicine workforce, but surprisingly little is typically done to promote academic medicine career awareness during the early stages of medical education. To raise awareness among medical students of the critical role an academic residency plays in pursuing a future academic career, we developed a workshop that describes what an academic residency entails and what to consider when selecting such a program. Methods The six-step Kern model was applied to develop a multimodal workshop to help trainees understand characteristics of and explore their interest in an academic residency program. The 60-minute workshop consists of a PowerPoint presentation, reflection exercise, and case scenarios to help trainees learn and apply new skills in selecting a residency program. The workshop was offered to diverse medical students at nine different medical schools across the country between July 2016 and May 2017. Results Of the 115 workshop participants who completed the evaluation form, over 95% agreed or strongly agreed that each of the learning objectives was met. A paired t test of learner responses pre- and postworkshop demonstrated significantly increased confidence in finding an academic residency position. Discussion This workshop fills an important gap in raising medical students' awareness of how to pursue an academic medicine career by highlighting the critical role of an academic residency program. Participants liked the use of vignettes and small-group discussion to better prepare them in exploring and benefiting from an academic residency position.